Optimization of a Perovskite-based Multilayer Microwave Absorber using an Equivalent Circuit Model - Arya, Aayushi (Engineering, Technology & Applied Science Research, 2023)
In this paper, the optimization of a perovskite-based multi-layer microwave absorber is performed to find an optimized value of the impedance step gradient from the refractive index of the constitutive layers. The optimization presented is unique as it is based on maximizing the dissipation and attenuation ability of the absorber along with a constraint of providing an efficient reflection loss in the absorber. This type of approach ensures the maximum absorption rate of the incident EM waves as the penetrating waves get fully dissipated. Objective and constraint functions are derived from the equivalent circuit model of the multi-layer absorber. The equivalent circuit model is formed using the inductive and capacitive effects across the dielectric and magnetic properties of the constitutive layers. The three layers are composed of perovskite materials with different refractive indexes such that the top layer serves as an impedance-matching layer followed by an alternate dielectric and magnetic layer. It is further shown how the capacitive and inductive losses are dominant over each other in the alternate lossy layers. Empirical relations are used to tabulate the refractive index of a range of perovskite compounds from which suitable combinations can be selected as per the obtained value of the step gradient function. The current work presents a simplistic method to design multi-layer microwave absorbers with different material combinations that are beneficial to the practical applications of microwave absorbers.